Process Evaluation of Routine Immunization (RI) And Growth Monitoring Services During Mamta Day (Village Health and Nutrition Day) In Sinor Block of Vadodara District, Gujarat, India - Parmar, Ajay; Parmar, Niyati; Pandya, Chandresh; Mazumdar, V S (National Journal of Community Medicine, 2014)
Background: Immunization plays a very important role in decreasing under-five mortality. Surveys carried out during NFHS and UNICEF revealed that there has been a decline in the coverage levels of different vaccines by as much as 15-40%. Objectives: To evaluate routine immunization and growth monitoring services in the sistrict. Material and Methods: A cross sectional observational study was conducted in Sinor block of Vadodara district, Gujarat. Two PHCs out of three PHCs of this block were selected and all thirteen sub centers of these PHCs were selected for monitoring of VHND. One village of each sub center was selected and monitored during Mamta Day for various components of vaccination and growth monitoring. Results: All Mamta day sessions were held according to micro plan with presence of all team members at all centres. However, supervisory visits were observed in only 23% of the sites. Necessary logistics and vaccines were available at all sites. Cold chain status was satisfactory. 23% of female health workers (FHW) faced problem in technique of giving BCG and Measles immunization. Time of reconstitution was written on BCG and Measles vials at 61.5% sites. Although Anganwadi workers (AWW) weighed children correctly, plotting was not satisfactory in 38 % of children. Conclusion: Supervision was lacking in majority of the sessions. Vaccine, logistics and cold chain maintenance was satisfactory. Repfesher periodical training need evident perticualrly of Immunization technique for FHWs and Growth plotting for AWWs.